Effects of a Military Parenting Program on Parental Distress and Suicidal Ideation: After Deployment Adaptive Parenting Tools - Gewirtz, Abigail H. (Suicide Life Threat Behav, 2016)
Few studies have examined whether parenting prevention programs might mitigate risk for suicidality in parents, yet parent suicidality is a strong risk factor for offspring suicidality. We report results from a randomized controlled trial of a parenting program for deployed National Guard and Reserve (NG/R) families with a school-aged child. Intent-to-treat analyses showed that random assignment to the parenting program (ADAPT) was associated with improved parenting locus of control (LOC). Improved parenting LOC was concurrently associated with strengthened emotion regulation which predicted reductions in psychological distress and suicidal ideation at 12 months post baseline. Results are discussed in the context of ongoing efforts to reduce suicide rates in military populations.